1999
DOI: 10.1074/jbc.274.12.7907
|View full text |Cite
|
Sign up to set email alerts
|

Ecto-ATPase Activity of α-Sarcoglycan (Adhalin)

Abstract: ␣-Sarcoglycan is a component of the sarcoglycan complex of dystrophin-associated proteins. Mutations of any of the sarcoglycan genes cause specific forms of muscular dystrophies, collectively termed sarcoglycanopathies. Importantly, a deficiency of any specific sarcoglycan affects the expression of the others. Thus, it appears that the lack of sarcoglycans deprives the muscle cell of an essential, yet unknown function. In the present study, we provide evidence for an ecto-ATPase activity of ␣-sarcoglycan. ␣-Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 58 publications
1
74
0
Order By: Relevance
“…In addition, ␤-dystroglycan and the ␣-and ␥-sarcoglycans have been shown to be tyrosine-phosphorylated upon stimulation with different ligands, implicating them as signaltransducing molecules (35,53). Specifically, ␣-sarcoglycan may function in bi-directional signaling in concert with the integrinadhesion system as well as possess ecto-ATPase activity (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ␤-dystroglycan and the ␣-and ␥-sarcoglycans have been shown to be tyrosine-phosphorylated upon stimulation with different ligands, implicating them as signaltransducing molecules (35,53). Specifically, ␣-sarcoglycan may function in bi-directional signaling in concert with the integrinadhesion system as well as possess ecto-ATPase activity (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, ␣-sarcoglycan is the best-studied member of the DG complex that has been implicated in signaling (35)(36)(37)(38). Thus, we further examined the expression and membrane localization of ␣-sarcoglycan, as a biochemical marker for the DG complex.…”
Section: Cav-3 Ko Mice Do Not Express Caveolin-3 In the Heart Andmentioning
confidence: 99%
“…Sarcolemma purified from rabbit skeletal muscles was used to determine the stoichiometry of the recombinant sarcoglycans. 22 …”
Section: Sds-page and Western Blottingmentioning
confidence: 99%
“…20 Recently, it has been shown that the cytoplasmic tail of ␥-sarcoglycan is phosphorylated after mechanical stimulation. 21 Lastly, ␣-sarcoglycan possesses an ectoATPase activity, 22,23 which could play a role in the extracellular ATP-dependent modulation of skeletal muscle contractility. 24 Studies on the assembly of the sarcoglycan complex, during the early stage of myotube differentiation, have provided evidence that sarcoglycans are co-translationally translocated in the endoplasmic reticulum (ER), where they associate during the transport through the Golgi to the plasma membrane.…”
mentioning
confidence: 99%
“…α-Sarcoglycan has been reported to have ectoATPase activity and it was suggested that the activity of P2X receptors may be modulated by α-sarcoglycan which buffers the extracellular ATP concentration [353]. Elevated concentrations of extracellular ATP and its activation of P2X receptors lead to Ca 2+ overload and muscle fibre death in the absence of α-sarcoglycan in sarcoglycanopathies.…”
Section: Muscular Dystrophymentioning
confidence: 99%